2021
DOI: 10.3390/vaccines9121489
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the WHO-Authorized COVID-19 Vaccines: A Rapid Review of Global Reports till 30 June 2021

Abstract: Large clinical trials have proven the efficacy of the COVID-19 vaccine, and the number of studies about the effectiveness rapidly grew in the first half of the year after mass vaccination was administrated globally. This rapid review aims to provide evidence syntheses as a means to complement the current evidence on the vaccine effectiveness (VE) against various outcomes in real-world settings. Databases (PubMed, EMBASE, and MedRxiv) were searched up to 30 June 2021, (PROSPERO ID: 266866). A total of 39 studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…This represents a lower risk of death in those who were vaccinated with at least one dose. Studies in the United Kingdom, United States, Israel, and Canada reported 64–100% effectiveness against death for one dose, and between 94% and 100% for two doses [ 17 ]. These studies evaluated the effectiveness of Pfizer, AstraZeneca, and Moderna vaccines, mostly against the alpha variant.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a lower risk of death in those who were vaccinated with at least one dose. Studies in the United Kingdom, United States, Israel, and Canada reported 64–100% effectiveness against death for one dose, and between 94% and 100% for two doses [ 17 ]. These studies evaluated the effectiveness of Pfizer, AstraZeneca, and Moderna vaccines, mostly against the alpha variant.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 23 preprints initially identified, 12 were published prior to submission of this article, and in only a few instances were minor updates to the VE results required. While other VE reviews have been published [ 10 , 11 , 12 , 13 , 14 ], our review was unique in that we (1) provided VE results for the first 6 months of global vaccine use and for only fully vaccinated participants, (2) examined VE for three population groups separately, and (3) plotted VE results to allow for direct comparison across disease presentation and disease severity categories by vaccine and by days after full vaccination. For a global population that was immunologically naïve to SARS-CoV-2, our focus on VE among fully vaccinated persons aged 16 years and older is valuable because it provides a baseline to compare the effectiveness of full vaccination in various populations around the world without having to factor in the influence of waning immunity [ 68 , 69 ], novel variants [ 70 ], or subsequent vaccine doses.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a review of published (i.e., peer-reviewed) SARS-CoV-2 VE articles, supplemented by preprints posted on preprint servers and reports published on websites of public health agencies during the first 6 months of COVID-19 vaccine availability. While other VE reviews have been published [ 10 , 11 , 12 , 13 , 14 ], our review is unique in that we (1) provided VE results for the first 6 months of global vaccine use and for only fully vaccinated participants, (2) examined VE for three population groups separately, and (3) plotted VE results to allow for direct comparison across disease presentation and disease severity categories by vaccine and by days after full vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination accelerated during the spring of 2021 in Europe and North America and has proven very effective in avoiding serious COVID-19 among vaccinated individuals, despite the emergence of more contagious virus variants, such as the Alpha and Delta variants [ 6 8 ]. Observational studies on vaccine effectiveness have suggested that mRNA vaccines reduce hospitalization with more than 85 percent for the Alpha and Delta variant [ 9 , 10 ], while vaccine efficacy has been shown to be even higher [ 11 ]. However, vaccine effectiveness varies between population groups [ 12 ].…”
Section: Introductionmentioning
confidence: 99%